Metronidazole Induced Xerostomia: A Case Report of an Elderly Patient - Gopineni, Divya; Maharajan, Mari Kannan; Diviti, Ranganayakulu (Journal of Pharmacy Practice and Community Medicine)
Xerostomia is a common but frequently overlooked condition that is typically associated with salivary gland hypofunction. It is one of the many side effects of some antihistamines, decongestants, and muscle relaxants. Incidence of xerostomia is higher among elderly patients particularly among those with kidney diseases. We present a case report of a 85-year-old female patient who suffered from metronidazole-induced xerostomia during her hospital stay.
Keywords: Xerostomia; Metronidazole; Geriatric; Salivary flow rate